Change of Interleukin-6, C-Reactive Protein and Soluble VascularCell Adhesion Molecule-1 Concentrations in HemodialysisPatients with Reprocessed Dialyzer - Nugroho, Pringgodigdo; Lydia, Aida; Panggabean, Marulam MP (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Cardiovascular disease is a major cause of morbidity and mortality in hemodialysis patients. In addition to traditional cardiovascular risk factors, non-traditional cardiovascular risk factors such as inflammation were also involved. Reprocessed dialyzer has been showed to induce less inflammation than new dialyzer, but data in diacetate cellulose membrane have not been presented. Methods. Twenty hemodialysis (HD) patients were enrolled. Pre and post study design was conducted to know post dialysis concentration changes of interleukin 6 (IL-6), C-reactive protein (CRP) and soluble vascular cell adhesion molecule-1 (sVCAM-1) at reuse 0, 5 and 10. Patients were recruited if medically stable, on maintenance HD >3 months, using reprocessed diacetate cellulose membrane by automated machine with mixture of periacetic acid and hydrogen peroxide solution. Urea reduction ratio (URR) and delivered dialysis dose were used to evaluate dialysis adequacy at reuse 0, 5, and 10. Results. CRP concentration was decreased. Median concentration of CRP at reuse 0, 5 and 10 were 3.55 mg/L, 2.97 mg/L and 2.92 mg/L, p=0.074. There were no significant changes of IL-6 concentration. Median concentration of IL-6 at reuse 0, 5, and 10 were 9.05 pg/ml, 10.64 pg/ml and 8.51 pg/ml, p=0.316. Concentration of sVCAM-1 was not changed significantly, with mean sVCAM-1 concentration 3078±786 ng/ml, 3260±836 ng/ml and 3154±631 ng/ml at reuse 0, 5 and 10,p=0.746. During use of reprocessed dialyzer through 10 times, there were no significant changes of hemodialysis adequacy using URR and Kt/V.